2019
DOI: 10.1002/hyp.13435
|View full text |Cite
|
Sign up to set email alerts
|

Spatial controls on the distribution and dynamics of a marginal snowpack in the Australian Alps

Abstract: Seasonal snowpacks in marginal snow environments are typically warm and nearly isothermal, exhibiting high inter‐ and intra‐annual variability. Measurements of snow depth and snow water equivalent were made across a small subalpine catchment in the Australian Alps over two snow seasons in order to investigate the extent and implications of snowpack spatial variability in this marginal setting. The distribution and dynamics of the snowpack were found to be influenced by upwind terrain, vegetation, solar radiati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 73 publications
(127 reference statements)
1
12
0
Order By: Relevance
“…Climate change is expected to result in a continued decline in snow cover area (SCA), an earlier snowmelt may lead to more frequent Spring flooding at the local scale (Hamlet and Lettenmaier, 2007), and Summer irrigation water shortages may occur in regions that are dominated by a large snow cover (Vano et al ., 2010; Viviroli et al ., 2011). In order to determine the response of snow cover to climate change, improve the precision of hydrological forecasting, and effectively manage water resources in snow‐dominated catchments, it is necessary to investigate the distribution and variation of water storage in the seasonal snowpack (Brown and Robinson, 2011; Bilish et al ., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Climate change is expected to result in a continued decline in snow cover area (SCA), an earlier snowmelt may lead to more frequent Spring flooding at the local scale (Hamlet and Lettenmaier, 2007), and Summer irrigation water shortages may occur in regions that are dominated by a large snow cover (Vano et al ., 2010; Viviroli et al ., 2011). In order to determine the response of snow cover to climate change, improve the precision of hydrological forecasting, and effectively manage water resources in snow‐dominated catchments, it is necessary to investigate the distribution and variation of water storage in the seasonal snowpack (Brown and Robinson, 2011; Bilish et al ., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The proportion of precipitation falling as snow at the area-weighted mean elevation of the catchment (1,783 m a.s.l. ), hereafter referred to as p snow , was estimated from the measured dry bulb air temperature using the method described by Bilish et al (2019).…”
Section: Methodsmentioning
confidence: 99%
“…and has been surveyed weekly throughout each snow season since 1954. Many previous studies of the Australian snowpack have used the Spencers Creek record as a primary input, although Bilish et al (2019) showed that using this site alone did not adequately represent the high degree of variability in the local area. It is therefore recognized that these SWE measurements may not be directly related to the total volume of water stored in the snowpack at Pipers Creek.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Australian Alps is a marginal snowpack environment (Bilish et al, 2018(Bilish et al, , 2019, where precipitation is crucial to agriculture, the generation of hydroelectric energy, and recreation. Water generated in the Australian Alps contributes to agriculture in the Murray-Darling Basin that accounts for 62 % of Australia's water use for irrigation (Australian Bureau of Statistics, 2020).…”
Section: Synoptic Weather Types and Trends In The Australian Alpsmentioning
confidence: 99%